An autopsy case of aortic root rupture with thin porcelain aorta during balloon-expandable transcatheter aortic valve implantation - Suzuyama, Hiroto (J Cardiol Cases, 2017)
A 92-year-old woman was transferred to our institute due to drug-resistant heart failure from severe aortic stenosis. She seemed to be a candidate for transcatheter aortic valve implantation (TAVI) because of her frailty and porcelain aorta. There were no severe calcified nodules in the left-ventricular outflow tract area. Because three-dimensional computed tomography analysis showed that her basal annulus area was 419 mm(2), a 26-mm SAPIEN XT (Edwards Lifesciences, Irvine, CA, USA) was selected for implantation. After deployment of the valve with 10% reduced volume, aortic root rupture occurred and her blood pressure fell due to acute cardiac tamponade. Emergent cardiac pericardial fenestration was done and drained blood was continuously returned to the circulation through percutaneous cardiopulmonary bypass. Despite strenuous efforts to save her life, she died 13 h after the event. An autopsy revealed a thin porcelain aorta and aortic root rupture with a fragile aortic wall. <Learning objective: Porcelain aorta is known to be a risk factor for perioperative stroke during surgical aortic valve replacement, and TAVI could be chosen for a treatment strategy in those cases. We present a case of aortic root rupture caused by unusually fragile aortic wall during TAVI and the lesson from the autopsy results.>